2011
DOI: 10.1099/jmm.0.031344-0
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antifungal susceptibilities and molecular typing of sequentially isolated clinical Cryptococcus neoformans strains from Croatia

Abstract: A collection of 48 clinical Cryptococcus neoformans isolates from Croatia was investigated retrospectively using in vitro antifungal susceptibility testing and molecular biological techniques to determine mating type and serotype by PCR and amplified fragment length polymorphism (AFLP) genotyping. These isolates were obtained from 15 patients: ten were human immunodeficiency virus (HIV)-negative (66.7 %) and five were HIV-positive (33.3 %). From five patients, only one isolate was available, whilst from the ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
27
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 34 publications
(57 reference statements)
12
27
1
Order By: Relevance
“…The present study shows that genotype AFLP1 and AFLP3 isolates are less susceptible to fluconazole than AFLP2 isolates. This genotypic difference was only recently observed in a Croatian study that found a similar result for fluconazole, although this difference was not significant between AFLP2 and AFLP3 isolates (31). The current study shows that there is a trend toward lower MIC values of amphotericin B for genotype AFLP2 isolates, similarly to that observed in the Croatian and Spanish studies (20,31).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…The present study shows that genotype AFLP1 and AFLP3 isolates are less susceptible to fluconazole than AFLP2 isolates. This genotypic difference was only recently observed in a Croatian study that found a similar result for fluconazole, although this difference was not significant between AFLP2 and AFLP3 isolates (31). The current study shows that there is a trend toward lower MIC values of amphotericin B for genotype AFLP2 isolates, similarly to that observed in the Croatian and Spanish studies (20,31).…”
Section: Discussionsupporting
confidence: 69%
“…The current study shows that there is a trend toward lower MIC values of amphotericin B for genotype AFLP2 isolates, similarly to that observed in the Croatian and Spanish studies (20,31). The Croatian and Spanish studies did not observe a significant difference between any of the tested antifungal compounds versus the AFLP genotypes, except for Spanish AFLP1 isolates that were less susceptible to amphotericin B than Spanish AFLP3 isolates (20,31). Similarly to our study, the Spanish study did not observe a significant difference between patient categories versus antifungal susceptibility.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In Croatia, nearly 900 HIV-infected persons had been registered from 1985, when HIV was first diagnosed, to December 2010 (13). The widespread use of highly active antiretroviral therapy (HAART) has lowered the incidence of cryptococcosis in HIVinfected persons in medically developed countries and in Croatia (11,13).…”
Section: Casementioning
confidence: 99%
“…The widespread use of highly active antiretroviral therapy (HAART) has lowered the incidence of cryptococcosis in HIVinfected persons in medically developed countries and in Croatia (11,13). Between 2005 and 2010, RCMDSDI verifi ed cryptococcosis in fi ve (33.3 %) HIV-infected patients and ten (66.7 %) non-HIVinfected patients (13).…”
Section: Casementioning
confidence: 99%